Answers

2014-10-11T19:37:40+08:00
Let 'x' be the weight of Elsa
    'y' be the weight of Bob
    'z' be the weight of Chris
x + y = 226 ---equation 1
y + z = 210 ---equation 2
x + z = 200 ---equation 3
rearranging equation 3 you'll have the value of x in terms of z
x + z = 200
x = 200 - z  ----equation 3'
substitute to equation 1
x + y = 226
(200 - z) + y = 226
y - z = 226 - 200
y - z = 26   ----equation 4
subtract equation 4 from equation 2
    y + z = 210
(-) y - z = 26
        2z = 184
         z = 92
substitute to equation 3'
x = 200 - z
x = 200 - 92
x = 108
substitute to equation 1
x + y = 226
y = 226 - x
y = 226 - 108
y = 118
0